Development of a scale battery for rapid assessment of risk and resilience. (June 2020) - Moore, Tyler M.; White, Lauren K.; Barzilay, Ran; Calkins, Monica E.; Jones, Jason D.; Young, Jami F.; Gur, Ruben C.; Gur, Raquel E.
Highlights: We combine twelve risk/resilience scales (212 items) and reduce them to a 46-item battery of seven sub-scales. We used factor analysis and computerized adaptive test (CAT) simulation to ensure that the abbreviated battery maintained acceptable measurement precision. Correlations of the full- versus short-form batteries with validity criteria revealed that almost all phenomena detected by the full 212-item battery were detected also by the abbreviated, 47-item form. The abbreviated battery is publicly available, and the full-text items are published here. Abstract: It is critical to understand the factors that increase risk for development of psychiatric disorders as well as promote resilience against disorders. The current study describes the development of a brief tool for risk/resilience assessment that takes a broad perspective of "risk" and "resilience" to characterize the phenomena, and assesses multiple factors that span intrapersonal, interpersonal, and wide-ranging external contexts. We administered twelve scales (212 items) to a diverse population comprising help-seeking and community participants ( N  = 298; 46% female) in the greater Philadelphia area. We used exploratory item-factor analysis to determine how items cluster across scales. After determining that a seven-factor solution was optimal, computerized adaptive testing (CAT) simulation was run to determine what would happen if the seven full-form factors were administered adaptively. These results were used to select items for short-form scales, producing seven final scales (items = 47). Validity was assessed by relating short-form scores to demographics, clinical diagnoses, scales, and criteria; these relationships were also compared to the relationships found with the original scales. Almost all effects detected by the twelve original scales were detected by the substantially abbreviated short-forms. The abbreviated battery shows promise for rapid assessment of multiple risk and resilience parameters, a necessity in large-scale studies.